The effects of four packaging systems and storage times on the survival of Listeria monocytogenes in shelf-stable smoked pork and beef sausage sticks and whole muscle turkey jerky - Lobaton-Sulabo, April Shayne S. (Kansas State University, 2012)
To validate how packaging and storage reduces Listeria monocytogenes (Lm) on whole muscle turkey jerky and smoked sausage sticks, four packaging systems, including heat seal (HS), heat seal with oxygen scavenger (HSOS), nitrogen flushed with oxygen scavenger (NFOS), and vacuum (VAC), and four ambient temperature storage times were evaluated. Commercially available whole turkey jerky and pork and beef smoked sausage sticks were inoculated with Lm using a dipping or hand-massaging method, respectively. There was no interaction on packaging and storage time on Lm reduction on smoked sausage sticks and an Lm log reduction of >2.0 log CFU/cm[superscript]2 was achieved in smoked sausage sticks packaged in HS, HSOS, and VAC. A >2.0 log CFU/cm[superscript]2 reduction was achieved after 24 h of ambient temperature storage, regardless of package type. NFOS was less effective in reducing Lm by more than 0.5 log CFU/cm[superscript]2 compared to HS, HSOS or VAC. After 30 d of ambient storage, Lm had been reduced by 3.3 log CFU/cm[superscript]2 for all packaging environments. In turkey jerky, Lm reduction was affected by the interaction of packaging and storage time. HS, HSOS, NFOS, or VAC in combination with 24, 48, or 72 h ambient temperature storage achieved <1.0 log CFU/cm[superscript]2. After 30 d at ambient temperature storage, Lm was reduced by >2.0 log CFU/cm[superscript]2 in HS and VAC, and could serve as a post-lethality treatment. Alternatively, processors could package turkey jerky in HSOS or NFOS in combination with 30 d ambient storage period as an antimicrobial process. Very little data has been published describing how packaging atmospheres affects Lm survival in RTE meat. The mechanism for Lm reduction under these conditions is not fully understood and additional research is needed.
Keywords: Packaging; Listeria monocytogenes; Jerky; Shelf-stable; Sausage sticks; Storage; Food Science (0359)